Cross-cultural adaptation and semantic validation of an instrument to identify palliative requirements in Portuguese - Santana,Marcella Tardeli Esteves Angioleti (2020)
ABSTRACT Objective To translate and make cross-cultural adaptation of NECPAL CCOMS-ICO© tool to Portuguese, and to analyze its semantic validity. Methods A methodological research about NECPAL CCOMS-ICO© tool cross-cultural adaptation, translated from Spanish into Portuguese and measurement of semantic validity. The cross-cultural adaptation process was conducted according to Beaton recommendations, including translation, translation synthesis, back-translation, and analysis of semantic, idiomatic, conceptual, and cultural equivalence of translated and back-translated tool versions, resulting in a pre-final version, which was submitted to a pre-test (n=35). Contend Validity Index was calculated to analyze semantic validity. Results Cross-cultural adaptation process allowed us to prepare the final version of this tool, which was named NECPAL-BR. Collected data from pre-testing step enabled the analysis of semantic validity. The Content Validity Index observed at this step was 0.94. Conclusion The semantic validity of the tool in its Portuguese version was confirmed; therefore, it may assist in screening chronic progressive disease patients, aiming to provide early palliative care. It may also be used to develop clinical and team performance indicators, and be employed as a care management tool designed to optimize resources.